The theory of Liberation from Brahmokta Vidisastra - Made Sri Putri Purnamawati (IAHN-TP Palangka Raya, 2022)
Dasaksara as it is widely known in Balinese Hindu society, is composed of a series of Panca Brahma (Sa, Ba, Ta, A, I) and Pancaksara (Na, Ma, Si, Wa, Ya) scripts. The ten holy scripts were first found in the book of Saiwa Religion in India where His